Coronary thrombolysis with intravenous anisoylated plasminogen-streptokinase complex BRL 26921. Issue 3 (March 1985) - Been, M; de Bono, D P; Muir, A L; Boulton, F E; Hillis, W S; Hornung, R
Abstract : BRL 26921 is a protected plasminogen-streptokinase complex with selective affinity for thrombus. When given intravenously within three hours of the onset of a first acute myocardial infarction angiographic patency of the infarct related vessel was seen in all 16 patients receiving the active drug compared with only two of 16 receiving a placebo. There was relative sparing of left ventricular function in the active treatment group with anterior infarction (mean left ventricular ejection fraction 37% compared with 23% for placebo), but no significant difference in left ventricular function between the active and placebo groups was seen in patients with inferior infarction. Intravenous BRL 26921 is highly effective in causing coronary reperfusion and may help to preserve left ventricular function when given early in the course of anterior infarction.